(untitled) (Swiss Medical Weekly, 2017)
AIMS We aimed to assess the cost effectiveness of sacubitril/valsartan compared to angiotensin-converting enzyme inhibitors (ACEIs) for the treatment of individuals with chronic heart failure and reduced-ejection fraction (HFrEF) from the perspective of the Swiss health care system. METHODS The cost-effectiveness analysis was implemented as a lifelong regression-based cohort model. We compared sacubitril/valsartan with enalapril in chronic heart failure patients with HFrEF and New York-Heart Association Functional Classification II–IV symptoms. Regression models based on the randomised clinical phase III PARADIGM-HF trials were used to predict events (all-cause mortality, hospitalisations, adverse events and quality of life) for each treatment strategy modelled over the lifetime horizon, with adjustments for patient characteristics. Unit costs were obtained from Swiss public sources for the year 2014, and costs and effects were discounted by 3%. The main outcome of interest was the incremental cost-effectiveness ratio (ICER), expressed as cost per quality-adjusted life years (QALYs) gained. Deterministic sensitivity analysis (DSA) and scenario and probabilistic sensitivity analysis (PSA) were performed. RESULTS In the base-case analysis, the sacubitril/valsartan strategy showed a decrease in the number of hospitalisations (6.0% per year absolute reduction) and lifetime hospital costs by 8.0% (discounted) when compared with enalapril. Sacubitril/valsartan was predicted to improve overall and quality-adjusted survival by 0.50 years and 0.42 QALYs, respectively. Additional net-total costs were CHF 10 926. This led to an ICER of CHF 25 684. In PSA, the probability of sacubitril/valsartan being cost-effective at thresholds of CHF 50 000 was 99.0%. CONCLUSION The treatment of HFrEF patients with sacubitril/valsartan versus enalapril is cost effective, if a willingness-to-pay threshold of CHF 50 000 per QALY gained ratio is assumed.